Laboratory diagnosis of bacterial meningitis. - Gray, L D (1992)
Bacterial meningitis is relatively common, can progress rapidly, and can result in death or permanent debilitation. This infection justifiably elicits strong emotional reactions and, hopefully, immediate medical intervention. This review is a brief presentation of the pathogenesis of bacterial meningitis and a review of current knowledge, literature, and recommendations on the subject of laboratory diagnosis of bacterial meningitis. Those who work in clinical microbiology laboratories should be familiar with the tests used in detecting bacteria and bacterial antigens in cerebrospinal fluid (CSF) and should always have the utmost appreciation for the fact that results of such tests must always be reported immediately. Academic and practical aspects of the laboratory diagnosis of bacterial meningitis presented in this review include the following: anatomy of the meninges; pathogenesis; changes in the composition of CSF; etiological agents; processing CSF; microscopic examination of CSF; culturing CSF; methods of detecting bacterial antigens and bacterial components in CSF (counter-immunoelectrophoresis, coagglutination, latex agglutination, enzyme-linked immunosorbent assay, Limulus amebocyte lysate assay, and gas-liquid chromatography); use of the polymerase chain reaction; and practical considerations for testing CSF for bacterial antigens.